Grupos Radicales Islámicos en la Red - González San Ruperto, Marta (Historia y Comunicación Social, 2005)
The development of Internet has open new possibilities of communication unthinkable only a few years ago. The information era has also reached people and groups which, due to their ideas, education or geographic location seem, at first sight, very far removed from the new technologies. However, the Net has become the meeting point for Islamic radical groups, as well as a tool of extraordinary importance in the spreading of their ideas on a world while scale and allowing them to keep the contact with their active members all around the planet. The object of this work is to analyse the main web sites of these characteristics, their contents, and their origin.
Keywords: Internet; Propaganda; Islamic Fundamentalism